Assessment of environmental impact of FOOD waste in Turkey. (20th January 2020) - Cakar, Belkis; Aydin, Serdar; Varank, Gamze; Ozcan, H. Kurtulus
Abstract: Food waste is a multifaceted problem that has negative impacts on the environment. Life cycle assessment (LCA) is a tool that shows these environmental impacts as quantifiable and is able to interpret the results with an integrated approach. In this study, LCA was used to analyze food waste in Turkey from a bottom up processing perspective. In order to assess the environmental impact of food waste on climatic, water, and energy resources, we calculated the embedded carbon, water, and energy footprints throughout the food supply chain in Turkey. Avoidable food waste was calculated as 16 Mt in Turkey in the year 2016. It is estimated that food waste in Turkey embodied 23.7 Mt of CO2 -eq, 6.2 × 10 9 m³ of water and 13.5 ×10⁴ TJ of energy. The results obtained by this research could be used to assess the linkage between food waste and the carrying capacity of resources. Graphical abstract: Image 1 Highlights: Avoidable food waste throughout the food supply chain was found as 16 Mt/y in Turkey. The carbon footprint of food waste was estimated 23.7 Mt CO2 -eq/y. The water footprint of food waste was estimated 6.2 × 10 9 m³/y of water. The energy footprint of food waste was estimated, 13.5 ×10⁴ TJ/y. It was concluded that the food waste means also wasted the limited resources.